Analiza lecznictwa uzdrowiskowego dzieci po leczeniu przeciwnowotworowym = Analysis of health spa treatment of children following cancer therapy - Wawryków, Agata; Lubkowska, Anna (Journal of Education, Health and Sport, 2016)
Wawryków Agata, Lubkowska Anna. Analiza lecznictwa uzdrowiskowego dzieci po leczeniu przeciwnowotworowym = Analysis of health spa treatment of children following cancer therapy. Journal of Education, Health and Sport. 2016;6(2):325-336. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.47034 http://ojs.ukw.edu.pl/index.php/johs/article/view/3413 https://pbn.nauka.gov.pl/works/718162 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.01.2016. Revised 12.02.2016. Accepted: 27.02.2016. Analiza lecznictwa uzdrowiskowego dzieci po leczeniu przeciwnowotworowym Analysis of health spa treatment of children following cancer therapy Agata Wawryków¹, Anna Lubkowska² ¹ Indywidualna Praktyka Fizjoterapeutyczna Agata Wawryków, 71 - 028 Szczecin, ul. Barbakan 1a/2 ² Zakład Diagnostyki Funkcjonalnej i Medycyny Fizykalnej, Wydział Nauk o Zdrowiu, Pomorski Uniwersytet Medyczny, 71-210 Szczecin, ul. Żołnierska 54 Dane autora korespondencyjnego: Agata Wawryków email: agata.wawrykow@gmail.com telefon: 505 599 002 mgr Agata Wawryków ¹, dr hab. n. zdr. Anna Lubkowska, prof. nadzw. PUM ² ¹ Indywidualna Praktyka Fizjoterapeutyczna Agata Wawryków, 71 - 028 Szczecin, ul. Barbakan 1a/2 ² Zakład Diagnostyki Funkcjonalnej i Medycyny Fizykalnej, Wydział Nauk o Zdrowiu, Pomorski Uniwersytet Medyczny, 71-210 Szczecin, ul. Żołnierska 54 Wykaz skrótów OUN Ośrodkowy Układ Nerwowy PNF ang. Proprioceptive Neuromulscular Facilitation, Torowanie Nerwowo - Mięśniowe ICD -10 ang. International Statistical Classification of Diseases and Related Health Problems, Międzynarodowa Klasyfikacja Chorób i Problemów Zdrowotnych Słowa kluczowe: lecznictwo uzdrowiskowe, dzieci, nowotwory złośliwe, fizjoterapia. Key Words: health spa treatment, children, cancer, physiotherapy. Streszczenie Wprowadzenie: W Polsce każdego roku rejestruje się około 1200 nowych zachorowań na nowotwory u dzieci. Wielu pacjentów po zakończonym leczeniu onkologicznym wymaga wieloetapowej, długotrwałej i systematycznej rehabilitacji. Istotną rolę w eliminacji późnych następstw leczenia pełnią placówki, umożliwiające odbywanie rehabilitacji zarówno fizycznej jak i psychospołecznej. W Polsce istnieje zaledwie jeden szpital uzdrowiskowy dla dzieci z chorobami nowotworowymi. Cel pracy: Celem pracy była analiza lecznictwa uzdrowiskowego dzieci po leczeniu przeciwnowotworowym na przykładzie Szpitala Hematologicznego Rehabilitacyjnego dla Dzieci „Orlik” w Kudowie Zdroju. Materiał i metody: Badaniu poddano grupę 3580 dzieci i młodych dorosłych (1865 dziewcząt oraz 1715 chłopców) w wieku od 1 do 21 lat (średnia wieku 11,53 lat, mediana 12 lat). Analizie retrospektywnej poddano pacjentów przebywających na turnusach rehabilitacyjnych w Szpitalu , Orlik" w okresie od 1 czerwca 2007 do 31 maja 2012 roku. Wyniki: W analizowanym okresie, w Szpitalu „Orlik”, dzieci po leczeniu przeciwnowotworowym stanowiły niespełna 26% wszystkich hospitalizowanych pacjentów. Najwięcej dzieci po leczeniu onkologicznym hospitalizowanych w omawianym ośrodku pochodziło z województw: pomorskiego, dolnośląskiego i lubelskiego, najmniej zaś z województw: podlaskiego, lubuskiego i warmińsko – mazurskiego. Najczęstszą przyczyną hospitalizacji pacjentów były zachorowania na nowotwory złośliwe układu krwiotwórczego. Wnioski: Pacjenci po leczeniu onkologicznym stanowią nieliczną grupę dzieci hospitalizowanych w analizowanym ośrodku. Najwięcej dzieci hospitalizowanych w Szpitalu Orlik pochodzi z wiodących ośrodków hematoonkologicznych w Polsce. Najmniej liczne grupy pacjentów pochodziły z najmniejszych województw położonych najdalej od ośrodka uzdrowiskowego. Summary Introduction: There is about 1200 new pediatric patients diagnosed with malignacies every year in Poland. Many of them requires a multi-stage, long-term and systematic rehabilitation after finished anti-cancer treatment. Specialized centers of physical and psychosocial rehabilitation take the main role in reducing the ate effects of anti-cancer treatment. There is only one rehabilitation center in Poland witch takes care of children with malignancies. Aim: The aim of this study was to analyze the health spa treatment of children after anti-cancer treatment on the example of Hematology Rehabilitation Hospital for Children "Orlik" in Kudowa Zdroj. Material and Methods: We studied a group of 3580 children and young adults (1865 girls and 1715 boys) aged 1 to 21 years (mean age 11,53 years, median 12 years) which were the patients in rehabilitation Hospital , Orlik" from 1 June 2007 to 31 May 2012. Results: In the analyzed period, in the Hospital "Orlik" children after anti-cancer treatment accounted for about 26% of all hospitalized patients. Most of children after oncological treatment came from the Pomerania, Lower Silesia and Lublin, least - from Podlaskie, Lubuskie and Warmia - Mazury. Most of children were suffering from hematologic malignancies. Conclusions: Patients after cancer treatment are a small group of children hospitalized in the reporting center. Most children hospitalized in the Hospital Orlik came from leading centers in Poland oncological.